Development of Multicultural Events Writing Teaching Materials with A Contextual Approach - Yanti Ritonga, Eka (Journal of Elementary School Education, 2023)
This research is motivated by students who lack creative thinking in solving problems in the material, students are required to understand the material, to develop students' thinking skills, researchers develop teaching materials based on teaching modules. This study aims to develop student teaching materials with a contextual approach to class VI news material at SD Negeri 017 Tambusai Utara with valid and practical criteria. This research is a type of research and development (Research and Development) with the ADDIE model. The research location was carried out at SD Negeri 017 Tambusai Utara. The time of the research was carried out in February 2022 - March 2022. The research population was class VI students. The research sample consisted of 20 students. Research data collection techniques using a questionnaire. The results showed that the validation of material experts was 73 with a percentage of 92.40%, media experts were 74 with a percentage of 94.87%, and the results of the validation of linguists were 57 with a percentage of 95%. Assessment of the level of practicality of teaching materials is known from the teacher response questionnaire and student response questionnaire, the results of the teacher response questionnaire were 92% (very practical) and the student response questionnaire was 85.2% (very good). Thus, teaching materials for writing multicultural news events with a contextual approach to class VI news materials meet valid and practical criteria for use in learning.